Konstruksi Manajemen Keuangan Islam (Suatu Gagasan) - Salim, Ubud (Jurnal Aplikasi Manajemen, 2009)
Islam have obligated each moslem especially those who have â€œworkingâ€ responsibility to work in islamic ways. Working for human being is a primary reason to gain wealth. Islam underpines (obligate) the â€œhalalâ€ aspect as an advice to solicit fortunes (rezeki), as well as the way it obtained and utilized on (managed and financed). Financial management is a managing the financial functions which are comprised of fund raising and capitalization. Therefore, finance management is often called equal to cash flow management. Fund capitalization commonly derived from inside and outside of the company. Company capitalization generally divided into short-term and long-term capitalization. A Suggestion to achieve effectivity and efficiency values in the implementation of both functions, Islam is exceptionally emphasizing the importance of â€œhalalâ€ aspect.Keywords: Working, Finance Functions, fund raising, fund capitalization